A Transcriptomic Model of Postnatal Cardiac Effects of Prenatal Maternal Cortisol Excess in Sheep - Antolic, Andrew; Richards, Elaine M.; Wood, Charles E.; Keller-Wood, Maureen (Frontiers in Physiology, 2019)
In utero treatment with glucocorticoids have been suggested to reprogram postnatal cardiovascular function and stress responsiveness. However little is known about the effects of prenatal exposure to the natural corticosteroid, cortisol, on postnatal cardiovascular system or metabolism. We have demonstrated an increased incidence of stillbirth in sheep pregnancies in which there is mild maternal hypercortisolemia caused by infusion of 1 mg/kg/d cortisol. In order to model corticosteroid effects in the neonate, we created a second model in which cortisol was infused for 12h per day for a daily infusion of 0.5 mg/kg/d. In this model we found that neonatal plasma glucose was increased and plasma insulin was decreased compared to those in the control group. Neonatal ponderal index and kidney weight were reduced, left ventricular wall thickness was increased. In this study, we have used transcriptomic modeling to better understand the programming effect of this maternal cortisolemia on the 2 week old heart. This is a time when both terminal differentiation and a shift in the metabolism of the heart from carbohydrates to lipid oxidation are thought to be complete. This model indicates suppression of fatty acid and ketone production and upregulation of angiogenesis in the epicardial adipose fat (EAT). The model indicates downregulation of RNA related pathways, but upregulation of ubiquitin-mediated proteolysis and protein targeting to the mitochondria in in the intraventricular septum (IVS) and left ventricle (LV). In IVS pathways the AMPK pathway and adipocytokine signaling pathways were also modeled as downregulated. Although peroxisomal activity is modeled as increased in EAT, it is decreased in LV and IVS; our previous metabolomic study of the newborn hearts from the 1 mg/kg/d study indicated changes in the plasmogens and phospholipids that are peroxisomal products. Our results suggest that lipid metabolism in the heart is altered, as are pathways related to proliferation and cardiac remodeling. Together, this model predicts that in utero exposure to excess maternal cortisol causes postnatal cardiac hypertrophy and altered responses to oxidative stress.